Analysis of Functional Elements of Public Debt Management - Tashbaev, Bobir (Annals of the Romanian society for cell biology, 2021)
According to him, the contractual nature of debt obligations has been clarified and "Under a loan agreement, one party (the lender) transfers to the other party (the borrower) money or other items marked with type characteristics, and the borrower gives the lender a lump sum or in installments of the same amount of money or the type and quality of the borrowed items. and undertakes to return the equivalent amount (amount of debt)". According to it, the state loan agreement clarifies the role of the state as a unilateral borrower and the participation of citizens or legal entities as creditors. [...]the source of public debt is the funds formed at the expense of personal income of legal entities and individuals (Sh; Sc). [...]the Civil Code of the Republic of Uzbekistan clarifies the content of public debt obligations, the subjects and regulations of public loan agreements. [...]monitoring, which is an important functional section of public debt managementThe Ministry of Finance of the Republic of Uzbekistan is responsible for the management.